Presos nas algemas do discurso do poder: a constituição dos sujeitos participantes do júri popular em Chapecó (SC) - Barp, Luiz Fernando Greiner (2018)
From a discursive investigation, this research aims to understand which knowledge and power arise in the juridical-penal discourse enounced at the court and how they compose the subjects who participate in the trial. The study corpus is built from ten jury trials that happened in Chapecó, Brazil, during the second semester of 2016. This collected material is analysed from Michel Foucault's inquietations and other authors who start from his provocations to formulate reflection on the discourse, knowledge, and power. Beginning the first chapter, we develop our theoreticmethodological referential from Foucault’s arquegenealogy, discuss about the juridical truth making, and deal with the court as a device which captures individuals turning them into subjects. Next, in the second chapter we offer juridical support to further reflection. From laws and codes that regiment jury trials in Brazil, we reflect on its current functioning, highlighting its transformation points and bounding which functions each subject has when participating of a trial. In the third chapter we identify the presence of a disciplinary power that, combined to scientific knowledge and other knowledge related to moral, objectifies the defendant and the witness, surveilling and punishing their actions. From that, both defendant and witness are then judged by questions that surpass the formality of the law, once they focus on their socio-historical conduct. Moving on to the fourth chapter, we notice remnants of a pastoral power and religious knowledge that, updated from biopower and its biopolitical strategies, affect the juror subject. This makes his decisions to be taken more with the intention of protecting the social body than actually judging a specific crime. Furthermore, we also identify how the juridical-penal discourse produces biographies with less value than others and, consequently, deaths are discursively authorized. In our conclusions, we abnegate a unitary theory of power as we notice how the court works more by the technique, normalization and control than by legal laws, extrapolating State’s sovereign ordens.